Purification and properties of thermostable xylanase and beta-xylosidase produced by a newly isolated Bacillus stearothermophilus strain. - Nanmori, T (1990)
We isolated a thermophilic bacterium that produces both xylanase and beta-xylosidase. Based on taxonomical research, this bacterium was identified as Bacillus stearothermophilus. Each extracellular enzyme was separated by hydrophobic chromatography by using a Toyopearl HW-65 column, followed by gel filtration with a Sephacryl S-200 column. Each enzyme in the culture was further purified to homogeneity (62-fold for xylanase and 72-fold for beta-xylosidase) by using a fast protein liquid chromatography system with a Mono Q HR 5/5 column. The optimum temperatures were 60 degrees C for xylanase and 70 degrees C for beta-xylosidase. The isoelectric points and molecular masses were 5.1 and 39.5 kDa for xylanase and 4.2 and 150 kDa for beta-xylosidase, respectively. Heat treatment at 60 degrees C for 1 h did not cause inhibition of the activities of these enzymes. The action of the two enzymes on xylan gave only xylose.